Greening Hotel, Greying Beliefs: The Unexpected Outcomes of Zero-Waste Management - Dina Lusianti; Ignatius Hari Santoso (Universitas Negeri Semarang, 2026)
This study examines the relationship among zero-waste management, perceived green capability and managerial belief in customer trust and booking intention within the hotel industry. The research model also incorporate hotel category (2 star, 3 star and 4 star) as a moderating construct. Using a quantitative survey design, data are collected from hotel manager to assess their perception of environmental practices and anticipated customer reactions. Data are analyzed using PLS –SEM to test the hypothesized direct and moderating relationship and to identify the strength and significance of each structural path. The result show that zero-waste management has a significant and positive effect on perceived green capability, demonstrating that environmental practices enhance the managers’ assessment of their hotel’s sustainability competence. However, perceived green capability does not significantly influence managerial belief in customer trust or booking intention. Additionally, zero-waste management is not found to significantly affect the managerial belief in customer trust or booking intention. Further, hotel classification also do not moderate the relationship between perceived green capability and the customer belief construct, indicating that sustainability capability is not viewed differently across hotel categories. These findings, reveal that environmental capability strengthen the internal strategic perception but does not translate directly into managerial expectation of customer behavior. This study is limited by its regional focus, the reliance on self-reported managerial perception and its cross-sectional design. Future research should incorporate the customer data, and also explore the alternatives moderating construct for better understanding about zero-waste management.